Tree Aboveground Carbon Mapping in an Indian Tropical Moist Deciduous Forest Using Object-Based Image Analysis and Very High Resolution Satellite Imagery - Singh, Neha; Nandy, Subrata; van Leeuwen, L. M. (Journal of the Indian Society of Remote Sensing, 2024)
Forests’ capability to sequester and store a large amount of carbon makes it imperative to assess the carbon stocked in them. The present study aimed to map the tree aboveground carbon stock of sal ( Shorea robusta ) forests of Doon valley, India using object-based image analysis (OBIA) of WorldView-2, a very high resolution satellite imagery (VHRS). The study evaluated different pan-sharpening techniques for improving the spatial resolution of WorldView-2 multispectral imagery and found that the high pass filter resolution merge technique was better compared to others. OBIA was used for image segmentation and classification. It enabled the delineation of tree crowns and canopy projection area (CPA) calculation. The overall accuracy of image segmentation and classification were found to be 72.12% and 84.82% respectively. The study unveiled that there exists a strong relationship between diameter at breast height and the CPA of trees as well as CPA and tree carbon. The average forest carbon density in the study area was found to be 108 Mg ha −1 . The study highlighted that OBIA of VHRS imagery coupled with field inventory can be efficiently used to quantify and map the tree carbon stock.